Path planning of an underwater robot for remote data collection - Toong, Chau Long (Nanyang Technological University, 2021)
In this report, optimal three-dimensional paths in the underwater environments with seabed terrain as obstacles and ocean current as disturbance for underwater vehicles are computed using a numerical optimized technique. Ocean current in the simulation will not only act as disturbance, it will be utilized for time-optimal path planning. Jaya algorithm will be used as an evolutionary algorithm for optimizing objective function in path finding. The underwater vehicle is modeled as a single point and the dynamic of the underwater vehicle will not be discussed in this report. The simulation results show the differences of the result regarding to the varying of various parameters such as number of generations, population size, number of variables per population. Multi-objective optimization algorithm based on posteriori approach will be proposed in this report in order to solve the multiple objective optimization problem simultaneously.